PUBLIC POLICIES IN BRAZIL: THE CASE OF THE PROGRAM OF ACQUISITION OF FOODS OF FAMILY AGRICULTURE IN THE STATE OF SAO PAULO, BRAZIL - Oliveira, Jonatan Alexandre de [UNESP]; Baccarin, Jose Giacomo [UNESP] (Univ Federal Fluminense, 2021)
The main objective is to analyze the organization of the Program of Acquisition of Food of Family Agriculture (PAA) in the agricultural space of the state of Sao Paulo, Brazil. We used as data source the actions of the Superintendence of National Supply Company CONAB-SP (2012). According with the actions of the PAA in the agricultural space of Sao Paulo, it was verified that the PAA presented a relative better performance in relation to the set of other regional superintendence; the Buy with Simultaneous Donation modality reaches the most expressive number of municipalities; the PAA has been applied with greater intensity in favor of the family farmers and settlers of more impoverished administrative regions; There is a strong link between the PAA and the agrarian settlements; the PAA seems to complement PRONAF, since is responds with greater intensity to those farmers with greater difficulties of access to the rural credit program. Taking into account the intentions expressed formally in the creation of the PAA, especially that of seeking to provide the lowest income family farmers. The analyzes of this work indicate that it has been fulfilled in the case of the state of Sao Paulo. Although the resources of the Program and the number of family farmers is still small relative to its potential audience
Keywords: Space Organization; Administrative Regions; Public Policy; Family Farming